(untitled) (Mūzikas akadēmijas raksti, 2024)
In this article, the focus is on churches in the small cities and rural areas in the historical Livland, especially the churches where the local congregation bought or received a small positive organ as a donation, and an organist was employed there during the 18th century. The research is based mainly on documents kept in the State History Archives of Latvia under the National Archives of Latvia and in contemporary periodicals. The main purpose of the article is to find out how much the organs spread in Livland during the 18th century. This research pays attention to the Latvian part of Livland, excluding Riga and its patrimonial area, becuse the musical life in Riga is widely described in Zane Gailīte`s monography Par Rīgas mūziku un kumēdiņu spēli (About the Riga’s music and the play of jesters, published in 2003).